2011
DOI: 10.1007/s00280-011-1803-9
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib pharmacokinetics and metabolism after oral administration to healthy male volunteers

Abstract: Afatinib displayed a complete mass balance with the main route of excretion via feces. Afatinib undergoes minimal metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 17 publications
3
93
1
2
Order By: Relevance
“…A clinical ADME study has also been reported for afatinib (Stopfer et al, 2012), another covalent binding EGFR-TKI. Similar to the data reported here, [ 14 C]-afatinib was excreted predominantly in feces (85.4% of dose), with urinary elimination a minor route.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical ADME study has also been reported for afatinib (Stopfer et al, 2012), another covalent binding EGFR-TKI. Similar to the data reported here, [ 14 C]-afatinib was excreted predominantly in feces (85.4% of dose), with urinary elimination a minor route.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-related AEs occurring in !10% patients in combined 20 mg (n ¼ 16) and 30 mg (n ¼ 2) afatinib once-daily dose groups, overall, and by maximum CTCAE grade Afatinib once daily þ trastuzumab MedDRA preferred term All, n (%) Grade 1, n (%) Grade 2, n (%) Grade 3, n (%) Patients with drug-related AEs 17 (94) 2 (11) 4 (22) 11 ( metabolism, and is excreted via the enterohepatic system. The in vitro metabolic profile of afatinib and pharmacokinetic data suggest no interaction between afatinib and cytochrome P450 substrates (20). Trastuzumab has a half-life of up to 28.5 days (21) and has shown additive effects with other agents, including taxanes and vinorelbine (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Determination of AFB alone was reported in two recent studies in human plasma using UPLC-DAD [10], LC-MS [11], with two other liquid chromatographic procedures published for its quantitation in tablets [12,13]. Moreover, one recent study reported AFB simultaneous determination with other TKIs namely, vandetanib, pazopanib, and dasatinib in human plasma using HPLC-DAD [14] with the AFB linearity range 0.7 -7.0 µgmL -1 , which is higher than its reported C max (maximum plasma concentration) value of 6.19 -7.58 ngmL -1 [11] and 11.6 -40.8 ngmL -1 after administration of single and multiple doses of different AFB concentrations [15]. On the other hand, individual CBZ quantification was reported using HPLC-UV [16], LC-MS/MS [17,18] in rat plasma with one study using micellar enhanced spectrofluorimetry in human plamsa [19].…”
Section: Introductionmentioning
confidence: 99%